Neuromechanical factors involved in the formation and propulsion of fecal pellets in the guinea‐pig colon. Issue 10 (6th August 2015) - Costa, M.; Wiklendt, L.; Simpson, P.; Spencer, N. J.; Brookes, S. J.; Dinning, P. G.
Abstract Background The neuromechanical processes involved in the formation and propulsion of fecal pellets remain incompletely understood. Methods We analyzed motor patterns in isolated segments of the guinea‐pig proximal and distal colon, using video imaging, during oral infusion of liquid, viscous material, or solid pellets. Key Results Colonic migrating motor complexes (CMMCs) in the proximal colon divided liquid or natural semisolid contents into elongated shallow boluses. At the colonic flexure these boluses were formed into shorter, pellet‐shaped boluses. In the non‐distended distal colon, spontaneous CMMCs produced small dilations. Both high‐ and low‐viscosity infusions evoked a distinct motor pattern that produced pellet‐shaped boluses. These were propelled at speeds proportional to their surface area. Solid pellets were propelled at a speed that increased with diameter, to a maximum that matched the diameter of natural pellets. Pellet speed was reduced by increasing resistive load. Tetrodotoxin blocked all propulsion. Hexamethonium blocked normal motor patterns, leaving irregular propagating contractions, indicating the existence of neural pathways that did not require nicotinic transmission. Conclusions & Inferences Colonic migrating motor complexes are responsible for the slow propulsion of the soft fecal content in the proximal colon, while the formation of pellets at the colonic flexure involves a content‐dependent mechanism in combination with content‐independent spontaneous CMMCs. Bolus size and consistency affects propulsion speed suggesting that propulsion is not a simple reflex but rather a more complex process involving an adaptable neuromechanical loop.